URBAN POVERTY IN BOGOTA: TERRITORY & REPRESENTATIONS - JOHAN ANDRÉS AVENDAÑO ARIAS (Bollettino della Società Geografica Italiana, 2019)
The main goal of this article is to identify the representations and imaginaries that Bogota inhabitants have regarding poverty, and its relation towards the territory. Representations and social imaginaries of poverty and inequality are contextualized in two specific zones in the city: Ciudad Bolivar and Usme. It is also analyzed the relationship between poverty and it representations in the territory. This article contains the findings after applying social-participant based cartography workshops as well as interviews performed to different actors involved, during 2010.